GV1001, hTERT Peptide Fragment, Prevents Doxorubicin-Induced Endothelial-to-Mesenchymal Transition in Human Endothelial Cells and Atherosclerosis in Mice - Wei Chen; Seojin Kim; Sharon Y. Kim; Cheyenne Beheshtian; Naryung Kim; Ki-Hyuk Shin; Reuben H. Kim; Sangjae Kim; No-Hee Park (Cells)
Doxorubicin is a highly effective anticancer agent, but its clinical use is restricted by severe side effects, including atherosclerosis and cardiomyopathy. These complications are partly attributed to doxorubicin’s ability to induce endothelial-to-mesenchymal transition (EndMT) in vascular endothelial cells, a critical process in the initiation and progression of atherosclerosis and cardiomyopathy. GV1001, a multifunctional peptide with anti-inflammatory, anti-cancer, antioxidant, and anti-Alzheimer’s properties, has demonstrated inhibition of EndMT. We investigated whether GV1001 could counteract doxorubicin-induced EndMT in endothelial cells and prevent atherosclerosis in a mouse model. The results revealed that GV1001 significantly suppressed EndMT induced by doxorubicin, likely through its protective effects on mitochondria. By mitigating mitochondrial damage, GV1001 reduced the accumulation of mitochondrial and cellular reactive oxygen species (ROS), repressed the activation of nuclear factor kappa B (NF-κB), and reduced the production of proinflammatory cytokines in endothelial cells. Additionally, GV1001 reduced systemic and vascular inflammation, lipid accumulation, and monocyte/macrophage infiltration within arterial walls in mice. In conclusion, GV1001 appears to prevent doxorubicin-induced atherosclerosis by safeguarding vascular endothelial cells from mitochondrial dysfunction, inflammation, and phenotypic changes. These findings suggest the potential of GV1001 as a therapeutic agent to mitigate the long-term cardiovascular side effects associated with doxorubicin treatment in humans.